2015
DOI: 10.1097/qad.0000000000000802
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of tuberculosis in post-mortem studies of HIV-infected adults and children in resource-limited settings

Abstract: Objectives:Tuberculosis (TB) is estimated to be the leading cause of HIV-related deaths globally. However, since HIV-associated TB frequently remains unascertained, we systematically reviewed autopsy studies to determine the true burden of TB at death.Methods:We systematically searched Medline and Embase databases (to end 2013) for literature reporting on health facility-based autopsy studies of HIV-infected adults and/or children in resource-limited settings. Using forest plots and random-effects meta-analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

9
292
1
4

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 321 publications
(306 citation statements)
references
References 42 publications
9
292
1
4
Order By: Relevance
“…The conduct of the study in multiple sites where early mortality rates are high and TB is endemic is a major strength, but the results may not be generalizable to settings where systematic TB screening is not performed or where limited resources prevent close follow-up and early TB diagnosis after ART initiation. In addition, the results from this study among outpatients initiating ART may be not be generalizable to sicker inpatient populations with higher mortality rates, where the prevalence of TB at autopsy has approached 50% 6 . However, randomized trials of empiric TB therapy in highly advanced patients in inpatient settings would address a different research question, and may have different concerns regarding equipoise.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The conduct of the study in multiple sites where early mortality rates are high and TB is endemic is a major strength, but the results may not be generalizable to settings where systematic TB screening is not performed or where limited resources prevent close follow-up and early TB diagnosis after ART initiation. In addition, the results from this study among outpatients initiating ART may be not be generalizable to sicker inpatient populations with higher mortality rates, where the prevalence of TB at autopsy has approached 50% 6 . However, randomized trials of empiric TB therapy in highly advanced patients in inpatient settings would address a different research question, and may have different concerns regarding equipoise.…”
Section: Discussionmentioning
confidence: 81%
“…Numerous studies done pre- and post-mortem have identified TB as the major cause of mortality in those with advanced HIV disease who are initiating ART in sub-Saharan Africa, India, Haiti and parts of South America, where our study took place 2, 6 . An additional hypothesized effect of empiric TB therapy relates to a potentially more durable TB preventive impact of isoniazid and rifampin compared to isoniazid alone 16 .…”
Section: Discussionmentioning
confidence: 99%
“…1 In East Africa, TB remains a major cause of death despite effective antibiotics, due in part to diagnostic delay and under-diagnosis. 1–4 Late or non-presentation to health facilities is one major cause of under-diagnosis that contributes to ongoing transmission and persistently high mortality rates. 5,6 Shifting TB screening out of health facilities and into communities, or “active” case finding, may reduce delays in TB diagnosis and undiagnosed disease.…”
Section: Introductionmentioning
confidence: 99%
“…1,2 There is evidence that antiretroviral therapy (ART) reduces the risk of acquiring TB among PLHIV even at higher CD4 cell counts, 3 and modeling using data from nine sub-Saharan African countries suggests that immediate ART will avert over a third of new TB cases by 2050. 4 A study from Zimbabwe in this edition of Public Health Action adds to the case for expanded ART coverage as a way to reduce the burden of TB.…”
mentioning
confidence: 99%